1995
DOI: 10.1038/378209a0
|View full text |Cite
|
Sign up to set email alerts
|

Movement and force produced by a single myosin head

Abstract: Muscle contraction is driven by the cyclical interaction of myosin with actin, coupled to the breakdown of ATP. Studies of the interaction of filamentous myosin and of a double-headed proteolytic fragment, heavy meromyosin (HMM), with actin have demonstrated discrete mechanical events, arising from stochastic interaction of single myosin molecules with actin. Here we show, using an optical-tweezers transducer, that a single myosin subfragment-1 (S1), which is a single myosin head, can act as an independent gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

44
475
9

Year Published

1996
1996
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 592 publications
(528 citation statements)
references
References 12 publications
44
475
9
Order By: Relevance
“…Alternatively, increased fragmentation of actin filaments might result from reduced stability of actin filaments in the presence of phosphate, however, only at low MgATP concentrations. This possibility appears unlikely as in trapping experiments in the three-bead arrangement (42) no evidence for reduced stability of actin filaments was found in the presence of 5 mM P i and M MgATP. 4 By the same line of arguments, the essentially unchanged dwell times of Cy3-EDA-ATP in the presence of phosphate and the reduced number of fluorescent events per field of view upon the addition of phosphate at low Cy3-EDA-ATP concentrations are also inconsistent with one of the concepts proposed by Warshaw et al (25).…”
Section: Discussionmentioning
confidence: 79%
“…Alternatively, increased fragmentation of actin filaments might result from reduced stability of actin filaments in the presence of phosphate, however, only at low MgATP concentrations. This possibility appears unlikely as in trapping experiments in the three-bead arrangement (42) no evidence for reduced stability of actin filaments was found in the presence of 5 mM P i and M MgATP. 4 By the same line of arguments, the essentially unchanged dwell times of Cy3-EDA-ATP in the presence of phosphate and the reduced number of fluorescent events per field of view upon the addition of phosphate at low Cy3-EDA-ATP concentrations are also inconsistent with one of the concepts proposed by Warshaw et al (25).…”
Section: Discussionmentioning
confidence: 79%
“…Single molecule mechanical measurements have suggested that the cross-bridge stroke is of the order of 4-17 nm [1][2][3], which is compatible with the conventional model for the crossbridge cycle [5]. However, there is no direct evidence of how many such strokes may be derived from the hydrolysis of a single ATP molecule.…”
Section: Introductionmentioning
confidence: 86%
“…A fundamental goal in understanding the mechanism of this process is to determine whether the ATPase activity is tightly coupled to the mechanical cycle of cross-bridge action. To this end, recent eflbrt has been directed towards in vitro motility assays where mechanical events have now been detected at the level of single molecular interactions between actin and myosin [1][2][3]. Likewise, the sensitivity of ATPase assays have been improved so that the long-lived myosin product complex (M.ADEP~) can be detected at the single molecule level [4].…”
Section: Introductionmentioning
confidence: 99%
“…In a thermally driven motor, no individual conformational change is required to account for all the work done. For example, the 4nm movement detected for an individual myosin molecule [9] may be regarded as a manifestation of the structural rearrangement that occurs within the motor domain to change its affinity to the track, rather than the stroke that carries out all of the work done; it may then be easier to understand how steps much longer than 4nm can be taken.…”
Section: Thermal Modelsmentioning
confidence: 99%